2018
DOI: 10.1186/s12974-018-1067-y
|View full text |Cite
|
Sign up to set email alerts
|

A clinical approach to new-onset psychosis associated with immune dysregulation: the concept of autoimmune psychosis

Abstract: Growing data point to the overlap between psychosis and pathological processes associated with immunological dysregulation as well as inflammation. Notably, the recent discovery of antibodies against synaptic and neuronal cell membrane proteins such as anti-N-methyl-d-aspartate receptor provides more direct evidence of the etiological connection between autoimmunity and subsequent hazard of psychosis. Here, we advocate the use of term “autoimmune psychosis,” as this term suggests that autoimmune disorders can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 65 publications
2
78
0
3
Order By: Relevance
“…Possible contributory factors include the lack of a control group in many studies, variability in terms of diagnosis and illness chronicity (frequently not reported in detail), and differences among studies with respect to how antibodies were tested, making interpretation of the results difficult, particularly given that there is ongoing debate about the most sensitive and specific methods for antibody detection. Regarding the latter point, the most frequently used method in the reviewed studies (the commercially available fixed CBA) is believed to have high specificity but lower sensitivity [14, 41]. Considering this, it is curious that those studies that found seropositivity in both patients and controls tended to use the commercial CBA, whereas those that only found seropositivity in patients used live CBAs.…”
Section: Discussionmentioning
confidence: 99%
“…Possible contributory factors include the lack of a control group in many studies, variability in terms of diagnosis and illness chronicity (frequently not reported in detail), and differences among studies with respect to how antibodies were tested, making interpretation of the results difficult, particularly given that there is ongoing debate about the most sensitive and specific methods for antibody detection. Regarding the latter point, the most frequently used method in the reviewed studies (the commercially available fixed CBA) is believed to have high specificity but lower sensitivity [14, 41]. Considering this, it is curious that those studies that found seropositivity in both patients and controls tended to use the commercial CBA, whereas those that only found seropositivity in patients used live CBAs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the strong immunoadsorbing property of the brain can lead to a binding of autoantibodies to their respective antigens, thereby limiting their detection in serum and CSF . Alternatively, autoimmunity may be due to an as-yet undefined innate or T-cell-mediated autoimmunity, rather than circulating autoantibodies (Najjar et al 2018).…”
Section: Antibody-negative Autoimmune Encephalitismentioning
confidence: 99%
“…Patient prognosis depends on the speed of disease detection, identification, and management [6]. Retrospective studies have found that psychiatric symptoms at first presentation were reported in 80-100% of cases, and subsequent management by psychiatrists in 70-80% [5].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…It is critical not to overlook appropriate neurological workup such as neuroimaging and EEG testing, as well as cerebrospinal fluid analysis, for cases with acute or subacute atypical onset of neuropsychiatric presentations including those dominated by acute psychotic symptoms [5]. Patient outcomes range from complete recovery to death after prolonged hospitalization [1].…”
Section: Introductionmentioning
confidence: 99%